557 Determining the efficacy of ADCC by the 3D-EX ex vivo platform utilizing tumoroids of fresh patient tumor samples with intact tumor microenvironment. (9th November 2020) - Kreahling, Jenny; Ehrhart, Jared; Iwanowycz, Stephen; Pabon, Mibel; Pastoor, Tina; Altiok, Soner
Abstract : Background: Antibody-dependent cell-mediated cytotoxicity (ADCC) is an effective tool where antibody-coated cells are targeted and killed by effector immune cells. The application of ADCC therapies has been expanded for both solid tumors as well as hematologic malignancies. However, the immunosuppressive mechanisms present in the immune tumor microenvironment (TME) pose a formidable challenge to immune cell efficacy in addition to hinderance of immune cell infiltration by tumor stromal elements. Hence, it is important to develop clinically relevant platforms to assess the efficacy of antibodies for ADCC. Here we utilized our 3D-EX platform using tumoroids of fresh patient tumor samples to assess ADCC-mediated tumor cell killing. Methods: All human tumor samples were obtained with proper patient consent and IRB approval. Fresh patient tumor tissue of various histologic types including non-small cell lung cancer (NSCLC) and colorectal cancer (CRC) was processed to generate uniform sized live 3D tumoroids measuring 150 µm in size. Treatment groups included cetuximab alone or in combination with nivolumab and/or ipilimumab. Culture supernatants were collected for multiplex analysis of cytokine release in media. Multiplex flow cytometry was used to assess the activation profile of tumor resident immune cells in combination with high-content confocal imaging to determine extent of ADCC-mediated tumor cell death in the intact tumor extracellular matrix. Results: Using fresh patient-derived tumor organoids, we observed ADCC-dependent death of EGFR expressing tumor cells. Flow cytometric analysis of immune cell populations demonstrated treatment mediated activation of resident immune cells, which coincided with cytokine profiles determined by Luminex multiplex cytokine analysis. Additionally, tumor cell killing observed through high-content confocal imaging and quantitative image analysis showed tumor cell death with the 3D tumoroids. Conclusions: In this comprehensive study we demonstrate that the 3D-EX ex vivo model is a robust system to assess the efficacy of ADCC and to develop novel therapeutic combinations with other immuno-oncology therapies. Furthermore, implementation of this platform in clinical studies may also allow for determination of the most effective combinatorial immuno-oncology therapy strategies for specialized individual patient care. Ethics Approval: The study was approved by Chesapeake IRB Pro00014313.